LC-MS/MS-based metabolomics approach identified novel antioxidant flavonoids associated with drought tolerance in citrus species - Rao, Muhammad Junaid; Feng, Bihong; Ahmad, Muhammad Husnain; Tahir ul Qamar, Muhammad; Aslam, Muhammad Zeshan; Khalid, Muhammad Fasih; Hussain, Sajjad; Zhong, Ruimin; Ali, Qurban; Xu, Qiang; Ma, Chongjian; Wang, Lingqiang (Frontiers in Plant Science, 2023)
Drought stress is one of the major environmental stresses that affect crop productivity. Citrus fruits are cultivated around the world that faces drought stress frequently during their growth and development. Previous studies showed that citrus plants biosynthesized flavonoid compounds in response to abiotic stress. In this study, we have quantified 37 flavonoid compounds from the leaves of three distinct citrus varieties including sour orange (drought tolerant), pummelo ‘Majia you pummelo’, and lemon (drought sensitive). The 37 flavonoids include 12 flavones, ten flavonols, six flavanones, five isoflavanones, and one each for chalcone, flavanol, flavanonol, and flavone glycoside. Drought stress differentially altered the flavonoid metabolism in drought-tolerant and sensitive citrus varieties. The kaempferol 3-neohesperidoside was 17 folds higher in sour orange (124.41 nmol/L) after 18 days of drought stress (18DDS) than lemon (7.33 nmol/L). In sour orange (SO), neohesperidin (69.49 nmol/L) was 1407 and 37 folds higher than pummelo (0.049 nmol/L) and lemon (1.84 nmol/L) respectively, after 18DDS. In SO, some flavonoids were significantly increased such as vitexin, neohesperidin, cynaroside, hyperoside, genistin, kaempferol 3-neohesperidoside, eriocitrin, and luteolin in response to drought stress, whereas in lemon these flavonoids were significantly decreased or not altered significantly in response to drought stress. Moreover, after 18DDS, the total contents of flavonoids and antioxidant activity were increased in SO as compared with pummelo and lemon. Gene expression analysis showed that flavonoid biosynthesis (PAL, CHI, FLS, GT1, F3H, F3’M, C4H, 4CL, FLS, FG2, FG3, and CYP81E1) genes were highly expressed in SO leaves than pummelo and lemon, after 18DDS. These outcomes showed that pummelo and lemon failed to biosynthesize antioxidant flavonoids, to cope with the prolonged drought stress whereas the sour orange biosynthesized fortified flavonoid compounds with increased antioxidant activity to detoxify the harmful effects of reactive oxygen species produced during prolonged drought stress.